Migracje ludności na Ziemiach Odzyskanych w latach 1945-1948 = Population migrations on the regained territories of Poland in the years 1945-1948 - Domke, Radosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The national politics of the communist government was of paramount importance in relation to the settlement and management of the Polish western and northern territories. The primary elements of the politics included: the eviction of the German population, the settlement of the Polish population and the incorporation of the native Polish population into the Polish nation. These issues were strongly connected with one another and were resolved simultaneously in the process of unification.
Keywords: Ziemie Zachodnie i Północne; Ziemie Odzyskane; migracje; wysiedlanie; 1945-1950